Global burden of myocarditis and cardiomyopathy in children and prediction for 2035 based on the global burden of disease study 2019 - Ba, Hongjun; Zhang, Daoqi; Guan, Shiyang; Zheng, Jinxin (Frontiers in Cardiovascular Medicine, 2023)
Background: Myocarditis and cardiomyopathy are commonly occurring cardiovascular diseases that seriously threaten children's health. It was urgent to update the global incidence and mortality of childhood myocarditis and cardiomyopathy，and to predict the incidence rate of 2035 by the Global Burden of Disease database. Methods: The Global Burden of Disease study data from 1990–2019 in 204 countries and territories were used to determine: global incidence and mortality rates of childhood myocarditis and cardiomyopathy from 0-19 by five age groups; relationship between sociodemographic index (SDI) and incidence and mortality rates by age group; and, based on an age-period-cohort model, the projected incidence of childhood myocarditis and cardiomyopathy for 2035. Results: From 1990–2019, global age-standardized incidence rate decreased by 0.1% (95%UI 0.0–0.1) to 7.7% (95%UI 5.1–11.1). Boys had higher age-standardized incidence of childhood myocarditis and cardiomyopathy than girls (9.12, [95%UI 6.05-13.07] VS 6.18, [95%UI 4.06-8.92]). Childhood myocarditis and cardiomyopathy affected 121,259 (95%UI 80,467–173,790) boys and 77,216 (95%UI 50,684–111,535) girls in 2019. At the regional level, SDI changes in most areas showed no meaningful difference. In East Asia and high-income Asia Pacific, increased SDI was associated with decreased and increased incidence rate, respectively. In 2019, 11,755 (95%UI 9,611–14,509) children died from myocarditis and cardiomyopathy worldwide. Age-standardized mortality rate decreased significantly by 0.4% (95%UI 0.2–0.6) to 0.5% (95%UI 0.4– 0.6). Number of deaths from childhood myocarditis and cardiomyopathy in 2019 was highest in the <5-year-old group (7442 [95%UI 5,834–9,699]). Myocarditis and cardiomyopathy incidence in 10–14- and 15–19-year-olds is projected to increase by 2035. Conclusion: Global data on childhood myocarditis and cardiomyopathy from 1990–2019 showed a decreasing trend in incidence and mortality, and an increasing trend in older children, especially in high SDI regions.